Effectiveness of Group Guidance Using Reframing Techniques to Reduce Toxic Disinhibition among Junior High School Students - Nidaul Ummah; Ahmad Syarqawi (MASI Mandiri Edukasi, 2025)
This study aims to determine the effectiveness of group guidance services using the reframing technique in reducing toxic disinhibition behaviour among eighth-grade students at SMP Negeri 2 Panyabungan. This behaviour involves aggressive and inappropriate expressions in digital interactions, often triggered by perceived anonymity and low social control. The study employed a quantitative approach with a one-group pretest-posttest pre-experimental design. A total of six students (n=6) identified with toxic disinhibition behaviour participated in the intervention. Data were collected using a 30-item questionnaire, validated with a Cronbach’s Alpha reliability score of 0.734. The intervention consisted of two group guidance sessions, each lasting 40 minutes. The results showed a reduction in the average score from 99.67 to 84.33. The Wilcoxon test yielded a significance value of 0.028 (p < 0.05), indicating a statistically significant difference before and after the intervention. The results suggest that the reframing technique effectively helps students reflect on their thinking patterns and build better self-control in digital contexts. This study recommends incorporating reframing into school counselling as a strategic approach to address deviant behaviour in the digital age. The findings also support using cognitive behavioural strategies in adolescent counselling interventions.